Out of the Middle East: New phylogenetic insights in the genus Tamarix (Tamaricaceae). Issue 5 (7th February 2019) - Villar, Jose L.; Alonso, M. Ángeles; Juan, Ana; Gaskin, John F.; Crespo, Manuel B.
Abstract: Tamarix is one of the taxonomically most complex genera among the angiosperms, and there is little consensus regarding its infrageneric classification. Here we present the most complete phylogenetic reconstruction of the genus to date. This includes a DNA phylogenetic tree based on nuclear ribosomal ITS, and a plastid DNA phylogeny based on three intergenic spacers ( trnS‐trnG, ndhF‐rpl32, and trnQ‐rps16 ). In total, both nuclear and plastid phylogenetic analyses include more than 70 samples of 39 species from 27 countries, which represent close to 60% of the diversity of the genus. Two complementary trees, based only on one plastid marker, are also included. The first, based on trnS‐trnG, is used to increase the number of species related to T. amplexicaulis . The second, based on ndhF‐rpl32, is used to investigate the separation between T. tetrandra and T. parviflora . The incongruence between the available infrageneric classifications and the molecular results is confirmed. A reticulate evolution is inferred from the trees, showing characters such as vaginate leaves appearing at different stages along the evolutionary history of the genus. The presence of T. canariensis outside the Canary Islands is cast into doubt, and all such records from NW Africa and Europe are here considered to belong to T. gallica . The results also suggest independence of T. karelinii from T. hispida, and T. parviflora from T. tetrandra . Relationships between a number of species are still not resolved, and additional studies will be needed to further refine the complex taxonomy of Tamarix .